The signification of estate agent as role modeL / Nur Shafiqah Abdul Manaf and Hairul Nizam Mansor - Abdul Manaf, Nur Shafiqah; Mansor, Hairul Nizam (2018)
Estate agent is a person that helps other people to find the property whether being on half of buyer or being of behalf of seller and the end would get a commission paid. So, in that time the agent is very important to ensure what the client wants will get. In real estate, the agent is very important. For example, if we want to run the business and need the shop to ensure the business that make can operate we need help from the agent to find the property. The study of this research is about the signification of estate agent as role model. This study is to determine the problem statement in this study is the number of the estate agent that has a registered license in Malaysia. Secondly is, the experience of work also is the main problem during to determine the successful estate agent. Its cause based on the experience it will determine whether the estate agent can be a successful estate agent or not. The interview that has been done is as the methodologies of this study. The results of this study should achieve two objectives of the study, which is to study the signification of estate agent as role model to identify the challenges face by the successful estate agent and to know what the criteria for successful estate agent in Malaysia.